Primary care practice in Ontario: An analysis of the factors that affect physician supply and activity - Donnelly, James G (University of Ottawa (Canada), 2004)
Health care reform is an essential and continuous process as a nation's medical system adjusts to meet changing needs in the population. It has been recognized that the Canadian health care system is in need of revolutionary change. Many other countries have had similar experiences to Canada in both resource shortages and reform process. The population of Ontario is growing and becoming older. Older persons place greater demands on the health care system. At the same time the Ontario physician workforce has decreased in size, increased in age and has more female entrants. Elderly physicians reduce their workloads as they reach the age of 65 years. Female physicians take on lower workloads than male physicians, especially in the early part of their careers. Over the past eight years there have been less entrants to Family Practice and more to specialty services. As well, in the past five years nearly 60 percent of Family Practice physicians have reduced their scope of care by limiting their practices. Taken together these observations demonstrate that while there is an increased need for primary and secondary care physicians there has also been a concurrent reduction of the number of physicians both in terms of census and also in terms of workload. In the past decade the Universities of Ontario have increased tuition fees significantly with respect to the other provinces. Financial pressures and control of hours (lifestyle control) may further limit the intake of post-graduate Family Practice physicians. Reversing these trends will require increasing the physician workforce and the development of programs to encourage entry into primary care.
Keywords: Business Administration, Management.; Health Sciences, Health Care Management.